Hubungan Pengetahuan Dan Sikap Ibu Dengan Pemberian Asi Ekslusif Di Puskesmas Silau Laut, Kec. Silau Laut Kab. Asahan Tahun 2023 - Rismawati Rismawati; Khairunnisa Situmorang; Lisdayanti Simanjuntak (Jurnal Anestesi, 2024)
Breast milk has many benefits, including reducing the risk of infectious diseases such as digestive tract infections, respiratory tract infections and ear infections. Breast milk can also prevent non-infectious diseases such as allergies, obesity, malnutrition, asthma and eczema. This research aims to determine the knowledge and attitudes of mothers regarding exclusive breastfeeding at the Silau Laut Community Health Center, Sea Glare District in 2023. This type of research is an analytical survey with a cross-sectional research design. The population is all pregnant women at the Silau Laut Community Health Center, Sea Glare District in 2023 as many as 38 people. The number of samples uses total sampling technique. The data analysis technique uses chi square. Based on the chi square test results, there is a relationship between maternal knowledge and giving exclusive breastfeeding with a P value = 0.002 < 0.05, there is a relationship between maternal attitudes and giving exclusive breastfeeding with a P value = 0.005 < 0.05. There is a relationship between mother's knowledge and attitudes and exclusive breastfeeding. It is recommended for mothers to be more proactive in seeking information to increase mothers' knowledge about exclusive breastfeeding, that giving breast milk to children can prevent breast cancer.